2007
DOI: 10.1007/s10791-007-9031-y
|View full text |Cite
|
Sign up to set email alerts
|

A review of text and image retrieval approaches for broadcast news video

Abstract: The effectiveness of a video retrieval system largely depends on the choice of underlying text and image retrieval components. The unique properties of video collections (e.g., multiple sources, noisy features and temporal relations) suggest we examine the performance of these retrieval methods in such a multimodal environment, and identify the relative importance of the underlying retrieval components. In this paper, we review a variety of text/image retrieval approaches as well as their individual components… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
34
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 95 publications
0
34
0
Order By: Relevance
“…It represents an area by roughness, directionality, repeatability and variability features over a certain spatial extent while color is a point property in an image [7]. Texture features are extracted by finding energy distribution in frequency domain by different techniques [39], [40], [41]. Gabor wavelet features are obtained using one such technique to retrieve and classify images and videos [42].…”
Section: Key Frame Featuresmentioning
confidence: 99%
“…It represents an area by roughness, directionality, repeatability and variability features over a certain spatial extent while color is a point property in an image [7]. Texture features are extracted by finding energy distribution in frequency domain by different techniques [39], [40], [41]. Gabor wavelet features are obtained using one such technique to retrieve and classify images and videos [42].…”
Section: Key Frame Featuresmentioning
confidence: 99%
“…As an approach, cross-modal associative learning has been applied to multimodal data retrieval although cross-modal learning is from cognitive science and neuroscience [6]. Snoek et al proposed concept-based video retrieval method [7] and Yan et al studied a multimodal retrieval approach including text and image for broadcast new video [8]. D. Li et al [9] suggested cross-modal association based factor analysis method as alternatives to Latent Semantic Indexing (LSI) and Canonical Correlation Analysis (CCA).…”
Section: Related Workmentioning
confidence: 99%
“…And cross-modal association learning has been applied to video data. Yan et al studied a text-image multimodal retrieval task on data of a broadcast new video [9] and Snoek et al suggested a concept-based video retrieval method [8]. Additionally, D. Li et al proposed a factor analysis method based on cross-modal association [10].…”
Section: Related Workmentioning
confidence: 99%